Discussion of Voluntary Corporate Disclosure: The Case of Interim Reporting - Schipper, Katherine (Journal of Accounting Research, 1981)
Katherine Schipper, Discussion of Voluntary Corporate Disclosure: The Case of Interim Reporting, Journal of Accounting Research, Vol. 19, Studies on Standardization of Accounting Practices: An Assessment of Alternative Institutional Arrangements (1981), pp. 85-88